Year-to-Year Adjustments of Performance Measure Weights: The Relevance of Prior Target Achievement - Margolin, Maximilian; Mahlendorf, Matthias D.; Schäffer, Utz (The Accounting Review, 2026)
We examine year-to-year adjustments of performance measure weights in managers’ incentive contracts. Using survey panel data on financial middle managers over four years, we document that higher target achievement on a given measure is associated with an increase in the measure’s relative weight for the subsequent year. We explore three potential explanations for this pattern: retention considerations, managerial influence, and gradual strategic shifts. Consistent with retention considerations, we find that shifts toward better performing measures are stronger for managers who outperform their peers and in firms facing greater labor market competition. Consistent with managerial influence, we find that shifts are also stronger for managers with greater influence on their incentives and in firms with lower incentive design transparency. We find, however, no support for the gradual strategy change explanation, as results do not show that shifts vary with managers’ involvement in strategic decision-making or subsequently observed strategy changes. Data Availability: The survey data used in this project are protected by a nondisclosure agreement.